Occupational safety health and environment management tools adoption among small medium entreprises - Khoo, Nee Kah (2023)
Occupational Safety Health (OSH) involves identifying and assessing workplace hazards, providing personal protective equipment, training employees on safety procedures, and monitoring and evaluating safety programs. OSH reduces workers' compensation costs and improves employee morale and productivity, while preventing injuries and illnesses. It also has wider societal benefits, by reducing the burden on healthcare resources. The COVID19 pandemic also impacted SMEs' ability or willingness to implement OSH. Occupational injuries are more common in SMEs manufacturing than in large corporations and Department of Safety and Health (DOSH) does not publicly disclose official SME accident case statistics. The management process of OSH is not adhered to in the small and medium manufacturing sector. The process on OSH for a cleaner environment has not been amended, and management's lack of technology adoption is due to a lack of budget and awareness towards a clean environment at work. Employers' lack of sufficient enforcement on OSH and environmental issues in the manufacturing sector is due to the lack of competent staff that has the related OSH certificate that qualifies them to carry out appropriate OSH enforcement. The objective of this research is to identify and address issues related to OSH compliance and create a clean work environment in the SMEs manufacturing sector. A clear vision and goals are important in achieving this objective, and accurate information on OSH is necessary for investigating and rectifying any compliance issues. Qualitative methods and descriptive research design with case study analysis focus in animal feeds manufacturing and exercises were used as a method of data accumulation; it involved an open-ended questionnaires (Respondents administrative questionnaire-RAQ) with 22 participants from the Melaka SMEs manufacturing sector. Hazard Identify Risk Assessment Risk Control (HIRARC) observation is from five participant companies. The semi-structured interview with 10 participants and the document study were conducted from secondary data sources for this research. The study emphasizes the importance of using HIRARC observation in OSH management to identify and control workplace hazards, and the crucial role of TEMIF in implementing new OSH technologies. The study found that SMEs in the manufacturing sector lacked awareness of OSH regulations and guidelines and did not have tools for implementing OSH clean environmental practices. Researcher proposes the Occupational Safety and Health Environment Management Tools (OSHEMT) for guided SMEs manufacturing sectors in OSH and environmental practices. SMEs manufacturing in Melaka should consider adopting OSHEMT technology, along with 5s and MUDA TORI techniques, to improve OSH management and create a safer work environment. Overall, this can enhance productivity and reduce costs linked to workplace accidents and injuries.